Complexity behind CO2 capture on NH2-MIL-53(Al) - Stavitski, Eli; Pidko, Evgeny A; Couck, Sarah; Remy, Tom; Hensen, Emiel J M; Weckhuysen, Bert M; Denayer, Joeri; Gascon, Jorge; Kapteijn, Freek (Langmuir, 2011)
Some Metal Organic Frameworks (MOFs) show excellent performance in extracting carbon dioxide from different gas mixtures. The origin of their enhanced separation ability is not clear yet. Herein, we present a combined experimental and theoretical study of the amino-functionalized MIL-53(Al) to elucidate the mechanism behind its unusual high efficiency in CO(2) capture. Spectroscopic and DFT studies point out only an indirect role of amine moieties. In contrast to other amino-functionalized CO(2) sorbents, no chemical bond between CO(2) and the NH(2) groups of the structure is formed. We demonstrate that the functionalization modulates the "breathing" behavior of the material, that is, the flexibility of the framework and its capacity to alter the structure upon the introduction of specific adsorbates. The absence of strong chemical interactions with CO(2) is of high importance for the overall performance of the adsorbent, since full regeneration can be achieved within minutes under very mild conditions, demonstrating the high potential of this type of adsorbents for PSA like systems.